2019
DOI: 10.1186/s12884-019-2202-1
|View full text |Cite
|
Sign up to set email alerts
|

Causes and contributory factors of maternal mortality: evidence from maternal and perinatal death surveillance and response in Ogun state, Southwest Nigeria

Abstract: BackgroundNigeria still ranks second globally in the number of maternal deaths. Most maternal death reviews in Nigeria are isolated research based reports from a single health facility. This study determined causes and contributory factors of maternal mortality in Ogun statefollowing a periodic State-widematernal and perinatal deaths surveillance and response (MPDSR) review.MethodsWe carried out a retrospective analysis of cases of maternal deaths notified (n = 77) and reviewed (n = 45) in health facilities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
83
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 10 publications
18
83
2
Order By: Relevance
“…The majority of the deaths were direct obstetric deaths due to haemorrhage, followed by eclampsia, obstructed labour and sepsis. This is consistent with findings of other studies including a WHO global estimate [1,6,[14][15][16]. One study from Mozambique and some other African countries identified sepsis as the second leading direct cause of death and HIV/AIDS was the most common indirect cause of death [17].…”
Section: Discussionsupporting
confidence: 89%
“…The majority of the deaths were direct obstetric deaths due to haemorrhage, followed by eclampsia, obstructed labour and sepsis. This is consistent with findings of other studies including a WHO global estimate [1,6,[14][15][16]. One study from Mozambique and some other African countries identified sepsis as the second leading direct cause of death and HIV/AIDS was the most common indirect cause of death [17].…”
Section: Discussionsupporting
confidence: 89%
“…An implication of this finding was that the community members, especially pregnant women mainly resorted to the utilisation of Traditional Birth Attendants (TBAs) during delivery. This comes at the backdrop that home deliveries with TBAs usually come with high maternal and neonatal mortality especially when they are untrained [27][28][29][30] which the participants in our study strongly alluded to. What makes the situation worse is that due to improper community entry, TBAs in our study were usually unwilling to refer cases they were unable to handle for skilled orthodox care and thereby increasing the chances of maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Okonofua et al [12], they found delay in arrival in hospital, the lack of antenatal care and patient's refusal to receive recommended treatment as the patient's associated causes of death, while delay in treatment, poor use of treatment protocols, lack of equipment and lack of skills by providers to use available equipment were the identified facility-related causes of death. In another study, by Sageer et al [13], the leading contributory factors of maternal deaths were inadequate human resource for health, delay in seeking care, inadequate equipment, lack of ambulance transportation, and delay in referral services.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have also found haemorrhage and pre-eclampsia and eclampsia as the leading causes of maternal deaths. Sageer et al [13] found figures of 43.4% and 36.9% of causes respectively in South-west Nigeria; Agan et al [8] found figures of 33.4% and 21.2% of causes respectively in South-south Nigeria; Tesfaye et al [14] found figures of 46.5% and 16.3% of causes respectively in Eastern Ethiopia. Nwagha et al [6] found sepsis as the commonest cause 25.8% before haemorrhage (23.7%) and pre-eclampsia/ eclampsia (12.4%).…”
Section: Introductionmentioning
confidence: 99%